Sử dụng các khung phân loại trong định hình cấu trúc lao động và đào tạo của Hoa Kỳ - Lê, Đông Phương (Viện KHGD Việt Nam, 2020)
The USA is very experienced in standardizdion of classification schemes. For the time being Anerican authorities are using various classification sớiemes for the specialization and professions of the minpower. This approach is a good one, worth of atention by Vietnamese agencies, especially when Vienam is involved in the globalization of education anc labour market. This article briefs readers about thì three mian classification being used in the us, tamely the Classification of Instructional Programs (CIP), the Standard Occupational Classification (SCC) and North American Industry Classification Systen (NAICS) as well as their applications.